2018
DOI: 10.1093/mnras/sty2345
|View full text |Cite
|
Sign up to set email alerts
|

The scatter of the M dwarf mass–radius relationship

Abstract: M dwarfs are prime targets in the hunt for habitable worlds around other stars. This is due to their abundance as well as their small radii and low masses and temperatures, which facilitate the detection of temperate, rocky planets in orbit around them. However, the fundamental properties of M dwarfs are difficult to constrain, often limiting our ability to characterise the planets they host. Here we test several theoretical relationships for M dwarfs by measuring 23 high precision, model-independent masses an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
88
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 94 publications
15
88
1
Order By: Relevance
“…Both of these objects have large uncertainties on their radii, but also orbit active stars which may have had some effect on the measurement of the radius of the brown dwarf. Parsons et al (2018) found that the scatter in the Mdwarf Mass-Radius relationship was 6.2±4.8 per cent, with only about a quarter of M dwarfs being consistent with models. They determined that there was no trend with either age or metallicity as to which M dwarfs are inflated.…”
Section: Discussionmentioning
confidence: 88%
“…Both of these objects have large uncertainties on their radii, but also orbit active stars which may have had some effect on the measurement of the radius of the brown dwarf. Parsons et al (2018) found that the scatter in the Mdwarf Mass-Radius relationship was 6.2±4.8 per cent, with only about a quarter of M dwarfs being consistent with models. They determined that there was no trend with either age or metallicity as to which M dwarfs are inflated.…”
Section: Discussionmentioning
confidence: 88%
“…It is also important to note, that the objects in Triaud et al (2017) are F, G and K type stars with M-dwarf secondary companions, and therefore do differ in nature to double M-dwarf binaries like NGTS J2143-38 . Of the double-lined M-Dwarf binaries listed by Parsons et al (2018), none have a greater eccentricity than NGTS J2143-38 , regardless of the period or semi major axis of the systems.…”
Section: Eccentricitymentioning
confidence: 94%
“…We compare the effective temperatures for both stars derived in §3.2 to the known temperatures of the sample of M-Dwarfs listed in Parsons et al (2018). This is shown in Figure 12, along with theoretical tracks (Baraffe et al 2015) for stars of this mass range.…”
Section: Mass Effective Temperature Relationshipmentioning
confidence: 96%
See 1 more Smart Citation
“…SDSS J2355+0448 was originally identified as a white dwarf candidate15 and later re-discovered as part of our systematic search of white dwarf plus low-mass main sequence binaries within the SDSS and LAMOST spectroscopic data bases16, 17 (see the optical spectrum in Figure 1). Eclipsing binaries offer the opportunity to measure directly the masses and radii of the two components with unprecedented precision16, 19. This is the case for the cool subdwarf in SDSS J2355+0448.…”
Section: Introductionmentioning
confidence: 99%